Paleogeography of the Tarsus Plain and Geoarchaeology of Gözlükule Mound in Light of a Multi-Proxy Analysis - Rifat İlhan; Aylin Karadaş; Sabah Kırallı; Serdar Vardar; Ertuğ Öner (Coğrafya Dergisi)
Gözlükule Mound is located in the northern Tarsus Plain . This study aims to reconstruct the paleoenvironment of Gözlükule Mound and the paleogeographic development of the Tarsus Plain. Core sediments taken from 19 drillings made between 2001-2002 are used to reveal the effects of natural environmental changes, with granulometric analyses, elemental analyses, and paleontological analyses being done for this purpose. In light of these analyses, the study interprets the natural environmental changes to the Tarsus Plain and the surroundings of Gözlükule Mound that occurred in the Holocene. In order to connect these developments to a certain chronology, a total of five radiocarbon-14 analyses were made with the support of Ege University Scientific Research Project Nos. SHD-2021-22452 and SYL-2020-22305. The paleontological, sedimentological, and elemental analyses, as well as the dating results of the sediment samples, were reevaluated, with the paleogeographic development of the region being revealed in accordance with the new data.